Rancang Bangun Solar Tracker Menggunakan Real Time Clock - Alfianto Putra B; Edy Suwarsono; Firmansyah (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2024)
Electrical energy supports daily activities. Replacement of electrical energy originating from PLN has been carried out in the Indonesia. However, this still faces several obstacles, one of which is that the effectiveness of solar panels is not yet optimal due to their (static) placement at certain angles. The development of solar panels is an urgent matter facing these challenges. This research aims to design a solar tracker system based on a real-time clock. This design method involves the Arduino Uno component to support tracking the sun's angle of incidence. The final stage of this research is the application of a solar tracker to solar panels. Based on equipment tests that have been carried out, it can be seen that static solar panels with a tilt angle of 10˚ produce an average output power of 3.5 watts. Meanwhile, solar panels with a solar tracker produce an average output power of 4.84 watts. Thus, it can be concluded that adding a solar tracker to solar panels can increase their effectiveness in producing electrical energy.